Development of Google Sites Based E-books on Sound Wave Material with STEM-PBL Model to Improve Mathematical Literacy and Critical Thinking Skills - Aditiyas, Saffa Ellok; Rosana, Dadan; Pratiwi, Ika; Nisa, Khairun; Hanindya, Yovita; Putri, Santri Adi; Chen, Diki (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
This research aims to: 1) Produce a Google Sites-based e-book using STEM-PBL model on sound wave material based on improving students' mathematical literacy and critical thinking; 2) Understand the practicality of Google Sites-based e-books using STEM-PBL model to sound wave material based on increasing students' mathematical literacy and critical thinking; 3) To find out the effectiveness of Google Sites-based e-books using STEM-PBL model to sound wave material based on increasing students' literacy and critical thinking. This research used ADDIE development model and was conducted at SMA Negeri 5 Yogyakarta. The number of subjects in this research was 250 students for the empirical test, 36 students for the limited trial, and 108 students for the extensive trial. The research instrument consists of product assessment sheet, practicality questionnaire, mathematical literacy and critical thinking test. The results show that: 1) e-book media based on google sites with STEM-PBL model developed worthy to be used in high school physics learning in particular sound wave material with good category by expert validator; 2) e-Book media with Google sites based on STEM-PBL model developed practically used in learning with the practical category; 3) e-books media with google sites based on STEM-PBL model was effective to enhance mathematical literacy and critical thinking abilities.